Typ rodziny a polskość dzieci za granicą - Ewa Lipińska (Postscriptum Polonistyczne)
The article aims at discussing the strategies of maintaining Polish traditions in different types of families leaving abroad: migration families, disconnected single-parent families, broken families, mixed families leaving in a country of one of the parents’ origin or a country foreign to both parents, as well as multinational patchwork families. In each type there are certain difficulties in transmitting the Polish language and culture, but they are caused by different reasons. The social status also determines the used code (a limited or developed one). It results in great language diversity among children living abroad and determines their attitudes towards Polishness.